"Click" Incorporation of Radical/Ionic Sites into a Reactive Block Copolymer: A Facile and On‐Demand Domain Functionalization Approach toward Organic Resistive Memory. Issue 1 (19th November 2015) - Suga, Takeo; Aoki, Kohei; Yashiro, Toshiaki; Nishide, Hiroyuki
Abstract : Reversible addition‐fragmentation chain transfer polymerization yields reactive block copolymers bearing the pentafluorophenyl ester (PFPA) group, and subsequent Click amidation using 2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl‐ and imidazolium‐functionalized primary amines produces the corresponding functional block copolymers, leading to installation of statistical radical‐ and ionic sites into the PFPA segment. The monolayered thin film devices fabricated using the obtained block copolymers exhibit repeatable switching of electric conductivity (on/off ratio > 10 3 ) under a bias voltage, which reveals that the coexistence of radicals and ions in the same spherical domain of the copolymer layer is a prerequisite for repeatable switching memory. Abstract : Click amidation of a reactive block copolymer bearing a pentafluorophenyl ester group with 2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl‐ and imidazolium‐functionalized amines provides the installation of statistical radical‐ and ionic sites into the reactive segment. Monolayer devices fabricated with the obtained block copolymers reveal that the coexistence of radicals and ions in the same spherical domain is a prerequisite for repeatable switching memory.